Caractéristiques sociodémographiques des minorités visibles - Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Longueil.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Demographic Profiles of Québec's English-speaking Communities Region of Montérégie and Longueuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Social Portrait of the Greenfield Park Borough (Ville de Longueuil) - Corporation de développement communautaire de l’agglomération de Longueuil (2020)